Re-conceptualize the public sphere and the public policies: a theoretical and practical necessity for the development of our society (Islas, 2022)
ABSTRACT: Introduction: The definition of the public, although it corresponds to the field of political philosophy has a direct incidence on the conceptualization and implementation of public policies. Critically explore the basis of its conceptualization in Western thinking will help us assume a constructive-creative posture in relation to the design, implementation and evaluation of public policies in Cuba. Methods: Critics to the association of the public sphere with the state, or with what is communal, critics to the definition of the what is communal as separated from the nature, and critics to the opposition between state and civil society, will be presented in this work, since they have direct impact in the formulation and implementation of the public policies for the development of our society. Results: The article serves as a reference for other countries in which both the government and some civil society organizations wish to detach themselves from the dictatorship of the American model of doing political science, since it comes from centers linked to the status quo proposed by the United States of America. Conclusions: The proposal of a liberal bourgeois thought regarding the public sphere imbricates whith the way of making political science in United States, producing inaccurate and lightly founded conceptualizations about the state, civil society, the public and prívate, among others which had been directly and indirectly influencing studies and political decisions have been or are currently carried out in our area.